NOBEL LECTURE: Protein Synthesis, Proteolysis, and Cell Cycle Transitions. Issue 5 (December 2002) - Hunt, Tim
Abstract : The discovery of the role(s) of protein synthesis and degradation in the operation of the cell cycle is described.